Corporate Social Responsibility Research Bibliometric Insight - Ag Kaifah Riyard Kiflee; Nornajihah Nadia Hasbullah; Nur Shahida Ab Fatah; Mohd Noor Azli Ali Khan (Human Resource Management Academic Research Society (HRMARS), 2021)
Given on the importance of social accounting for sustainable development, this study objectives are to investigate the global trends of CSRD from the perspective of publications outputs, co-authorship, countries, and authors co-occurrences keywords. CSR activities and disclosure practices are arguably important as mean to improve social communication between company to stakeholder. It is being emphasized that, understanding the subject of interest and widening the networking is important to improve the research from many perspectives. From 1959 to 2019, a total of 181 articles were extracted from Scopus database for analysis purpose. Result analysis suggested that, publications on CSRD have experienced positive upwards from 2013 until 2019, contributing to total cumulative of CSRD articles. More than half of CSRD articles were published by UK researchers, China and Malaysia, leading other countries. Due to the nature of research, most of the CSRD articles were contributed by academic institutions. In an attempt to further CSRD research, Islamic banks, performance and managerial ownership were seen as potential topics to be expanded by future research.